Effects of atmospheric carbon dioxide, oxygen and ethylene on the growth and quality of mungbean sprouts - Ahmad, Siti Hajar; Mohamad, Mahmud Tengku Muda (1987)
A study was conducted to evaluate the Influence of different combinations of carbon dioxide, oxygen and ethylene on the growth of sprouts from four mungbean cu1tivars. Sprouts produced using CO2 and 02 at 5% to 10% and 10% to 15%. respectivelv, were shorter than those produced without any treatment. However, they were still undersirable because the root length was too long and the hypocotyl diameter too small. The different gas mixtures alone, or In combination wlth ethylene, still did not yield the desired sprouts. The desired hypocotyl diameter and length of sprouts were obtained when the ethylene level in the air system was increased to 5.0 u liter/liter